Synthesis, Characterization and Alpha Glucosidase Inhibition activity of new Phthalimide Derivatives - Hassan ALi; Mohammed H. Mohammed; Sajida H. Ismeal (College of Pharmacy University of Baghdad, 2018)
Three of imide intermediate products  were synthesized by reacting of phthalic anhydride with glycine (2a), and tetrachloro phthalic anhydride with glycine , (S)-2-[(tert-Butoxycarbonyl)amino]-3-aminopropionic acid ( 2b,c)  respectively   in  dry toluene  with azeotropic removal of water using Dean- stark apparatus then carboxyl functional group activated by refluxing with  thionyl chloride, the resulted acid chloride (3a-c) were reacted with different amine (5-flourouracil, 4-chloroaniline, 4-bromoaniline, 2-amino thiazole, and pyrrolidine) (4a-e) , the   resulted products consider as the end products (5a-j) while  the compounds (5k-o) required further reaction to deprotect aliphatic amine this achieved by treating the compounds with TFA to remove tert-Butoxycarbonyl group (6a-e). The alpha glucosidase inhibitory activity of some synthesized compounds (5a, 5f, 6a) were tested by using  -glucosidase from Saccharomyces cerevisiae, p-nitrophenol glucopyranoside (pNPG)  used as substrate and acarbose used as standard. All these test compounds shows   excellent inhibitory activity according to IC50 values which is ranging from (4.61-7.32).